Enhancer of zeste acts as a major developmental regulator of Ciona intestinalis embryogenesis - Le Goff, Emilie (Biol Open, 2015)
The paradigm of developmental regulation by Polycomb group (PcG) proteins posits that they maintain silencing outside the spatial expression domains of their target genes, particularly of Hox genes, starting from mid embryogenesis. The Enhancer of zeste [E(z)] PcG protein is the catalytic subunit of the PRC2 complex, which silences its targets via deposition of the H3K27me3 mark. Here, we studied the ascidian Ciona intestinalis counterpart of E(z). Ci-E(z) is detected by immunohistochemistry as soon as the 2- and 4-cell stages as a cytoplasmic form and becomes exclusively nuclear thereafter, whereas the H3K27me3 mark is detected starting from the gastrula stage and later. Morpholino invalidation of Ci-E(z) leads to the total disappearance of both Ci-E(z) protein and its H3K27me3 mark. Ci-E(z) morphants display a severe phenotype. Strikingly, the earliest defects occur at the 4-cell stage with the dysregulation of cell positioning and mitotic impairment. At later stages, Ci-E(z)-deficient embryos are affected by terminal differentiation defects of neural, epidermal and muscle tissues, by the failure to form a notochord and by the absence of caudal nerve. These major phenotypic defects are specifically rescued by injection of a morpholino-resistant Ci-E(z) mRNA, which restores expression of Ci-E(z) protein and re-deposition of the H3K27me3 mark. As observed by qPCR analyses, Ci-E(z) invalidation leads to the early derepression of tissue-specific developmental genes, whereas late-acting developmental genes are generally down-regulated. Altogether, our results suggest that Ci-E(z) plays a major role during embryonic development in Ciona intestinalis by silencing early-acting developmental genes in a Hox-independent manner.